ANALISIS PENGARUH KUALITAS PELAYANAN INTI DAN KUALITAS PELAYANAN PERIFERAL TERHADAP WORD OF MOUTH MELALUI KEPUASAN PELANGGAN CATERING IDA, SEMARANG - Prabowo, Abi; Santoso, Suryono Budi (Faculty of Economics and Business Diponegoro University, 2016)
Problems that occur in Catering Ida was there a decrease in the number of sales and an increase in the number of complaints during the year 2013, which indicates an increase in customer dissatisfaction which cause customers not interested in re-purchase. Prasurvey based on the results that have been done, it can take several variables thought to influence the customer satisfaction is the quality of core services, and service quality peripherals. So that the formulation of the problem in this research is how to increase customer satisfaction and word of mouth customers Catering Ida. This study aimed to analyze the influence of the core service quality and service quality peripherals to satisfaction and word of mouth customers Catering Ida. The population used in this study are customers Catering Ida. The sampling technique used was purposive sampling. Criteria samples taken Catering Ida is the customer who has made a transaction more than one time, amounting to a minimum of 97 customers. Methods of data collection in this study using a questionnaire. Methods of data analysis using multiple linear regression analysis. Based on this research, the quality of core services and service quality peripherals positive effect on satisfaction and word of mouth customers Catering Ida, while satisfaction has positive influence on word of mouth customers Catering Ida. Customer satisfaction is able to mediate the effect of core service quality and service quality peripherals to word of mouth.